A case of autoimmune hypothyroidism presented as overlap syndrome of mixed connective tissue disorder - Malik, Atiullah I.; Ponvijaya, Yadav; Shivnitwar, Sachin; Pahuja, Anuj (International Journal of Research in Medical Sciences, 2020)
Mixed connective tissue disease is a distinct complex overlap disorder characterised by combination of clinical features of systemic lupus erythematosus, systemic sclerosis, polymyositis and rheumatoid arthritis. Higher levels of anti-U1-ribonucleoprotein (anti-U1RNP) antibody has been found in these patients. 39 year old female, known case of hypothyroidism, came with complaints of multiple joint pains with swelling associated with morning stiffness of fingers since last 2 years. She also had dryness of skin, loss of appetite, constipation, difficulty in swallowing and dyspnea on exertion since last 2 months. Considering the joint pains an antinuclear antibody (ANA) was sent. She turned out to be RNP, Sm, Ro 52, Mi-2 positive. Anti-CCP, rheumatoid factors (RA), Raynaud’s phenomenon all were positive. Rheumatologist opinion was taken and she was diagnosed as mixed connective tissue disorder with hypothyroidism. Patient was successfully treated with immunosuppressants and supportive measures and responded well to tablet methotrexate, prednisone, nifedipine and hydroxychloroquine. Our patient had one major and 3 minor criteria: anti RNP antibody positive, Raynaud’s phenomenon, swollen fingers and synovitis. Thus, diagnosed as mixed connective tissue disease.